Bridging the Gap between Clinical Practice and Research Part I: Findings of a Pilot Study on Daniel Stern's 'Moments of Meeting' from the UKCP's Practitioner Research Network. (23rd April 2020) - Harris, Tirril; Lepper, Georgia; Cheetham, Brian; Crowther, Catherine; King, Desmond; Ryde, Julia
Abstract : Psychotherapists continue to be wary of researchers who enter the clinical domain and their methodologies, which can seem opaque and alien to clinical practice. The following is a report on a pilot project, supported and enabled through the Practice Research Network of the UK Council for Psychotherapy (UKCP), to explore whether adopting the role of researcher on the therapy process, using their own clients, could help to dissipate this discomfort. Findings were anticipated concerning two groups of issues. First, we sought to examine whether, and how, a 'moment of meeting' (MoM) might impact on the therapy, and its outcomes. Second, whether, and how, undertaking the role of researcher with one's own clients might affect clinical practice, and how systematic reflection on observations from clinical practice might provide rich evidence in the development of the MoM concept. We report on two broad issues arising from the project. First, using the data collected by the research team in a mixed method study of their own cases, we examine the relationship of the process variable MoM to clinical outcome. Relationships between other process variables were also investigated, using both established measures and a new, post‐therapy interview developed by the team during the project. Second we explore the experience of the participant clinicians undertaking research on their own, and their colleagues', clinical practice. Finally we consider the learning taken from this pilot project, making recommendations for taking our experience of clinician–research collaboration further.